CREDIT COMFORTABILITY AND MICROFINANCE: A FIELD STUDY TO DETERMINE PEOPLES’ PERCEPTION ABOUT CONVENTIONAL AND ISLAMIC MICROFINANCE IN PAKISTAN - Muhammad MERAJ (Türkiye İslam İktisadı Dergisi)
This paper examines credit comfortability and the role of microfinance, based on a field study which determines the perceptions of Pakistani people regarding conventional (interest based) and Islamic (interest free) microfinance. Conventional microfinance is not naïve in poverty alleviation but an in-depth analysis is needed to assess its success in poverty hit countries like Pakistan. The goals of poverty alleviation through microfinance in Pakistan have not fully achieved as majority of population have been living at below poverty line for many years. The primary data has collected through questionnaire with street intercept method during July’2014 to October’2014, in Karachi, Pakistan.